The concept of digital reality and its heuristic potential in the explication of threats of digitalisation - Kasiankou, Aliaksandr Yu. (Journal of the Belarusian State University. Sociology, 2023)
The potential of the concept of digital reality is demonstrated in the explication of the negative consequences associated with digitalisation. The work reveals a list of threats and their essence by analysing three interrelated processes of introducing digital technologies (computerisation, networking and virtualisation), as well as analysing the resulting new information reality. It is noted that the possibility of considering the process of digitalisation in integrity makes the concept of digital reality an effective theoretical and methodological system for concretising the threats of our time.